The Effect of Ease and Trust Using E-commerce on Purchasing Decision for Online Binjai District Attorney Employees - Sinta Marito Elisabet; Wan Rizca Amelia; Teddi Pribadi (Universitas Medan Area, 2022)
This study aims to determine how the influence of ease and trust in using e-commerce onpurchasing decisions for online employees of the Binjai District Attorney's Office. The type of research used is quantitative research, where the variables are measured using the Likert scale method. Data collection in this study was carried out by means of a list of questions (questionnaires), interviews (interviews), and direct observation. Sampling was done by totalmethod sampling, where the entire population was used as a sample of 45 people. Datacarried out using the SPSS (processing wasstatistical program for social scienceapplication) version 21.0. The hypothesis testing technique in this study uses multiple linear regression. Previously, the validity test, reliability test, and classical assumption test were conducted first. The results of this study indicate that: (1) Partially, the variable ease of using e-commerce has an effect onpurchasing decisions for online employees of the Binjai District Attorney's Office. (2) Partially, the trust variable using e-commerce has an effect onpurchasing decisions for online employees of the Binjai District Attorney's Office. (3) Simultaneously there is a positive and significant influence between the variables of convenience and trust in using e-commerce onpurchasing decisions for online Binjai State Attorney's employees.